Barcoding of ToLCV Resistant Tomato Germplasm in Bangladesh (Plant Tissue Culture and Biotechnology, 2020)
The current study was carried out to confirm the existence of the ToLCV resistant genes (Ty-1 to Ty-5) in the germplasm using molecular markers and to identify at the genomic level following phylogenetic relationships analysis among some local tomato germplasm using DNA barcoding. Most of the tomato germplasm (Ten out of 14) contain the dominant Ty-genes as revealed by PCR analysis. “Barcoding” of the non-coding plastid trnH-psbA intergenic spacer region, three plastidal regions: rbcL, rpoB, rpoC1, spacer region of nuclear genome ITS and a mitochondrial region matK were employed following PCR and sequence analysis of the germplasm. Among all the barcode genes, rpoB, rbcL, trnH-psbA and ITS were leading candidates for successful amplification and used for the identification of the germplasm as S. lycopersicum in multi-locus identification based on their sequences. Neighbor-Joining phylogenetic tree was constructed in which the germplasm were clustered into five main clades. The current study was successful to establish an efficient barcoding protocol for the correct identification of tomatoes and was capable of establishing elite gene source(s) for biotic stress resistance tomato varieties which would serve as potential donor plants in modern breeding programs.Plant Tissue Cult. & Biotech. 30(1): 107-117, 2020 (June)